Dampak Nikah Paksa Karena Hak Ijbar (Studi Kasus di Kel. Teritip Balikpapan Timur) - Nurhayati Nurhayati; Paryadi Paryadi (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2022)
Forced marriages due to ijbar rights have become commonplace among the people in the Teritip Village. Ijbar is coercion in the sense of marriage which is fully owned by the guardian, namely the father or grandfather. Scholars in viewing forced marriages have different opinions from the object of forced marriage to whether the marriage is legal or not. In this case, the impact of forced marriage because the right of ijbar has two connotations, negative and positive. Some have a bad or negative impact and some have a good impact. This research is a type of field research, which is qualitative in nature, by describing and analyzing the impact of forced marriage due to the right of ijbar. Data collection techniques that researchers use are observation, interviews and literature study. Then the presentation of the data that has been found in descriptive form, and drawing conclusions The results of the research that the researchers got based on the data found, the researchers concluded, there were two different impacts from the cases that the researchers studied. There are cases that end happily and have a positive impact, some end in failure and have a negative impact. The negative impact outweighs the positive impact. The positive impacts are: Parents help their children to find a man who is well known by their parents too, children don't have to worry about a mate who doesn't come because parents help and engage in choosing a mate for their child. The negative impacts are: There is no sense of love and affection that arises in the household based on a sense of compulsion, the household becomes inharmonious and uncomfortable to live and what is more fatal is the occurrence of divorce, an act that although lawful but is hated by Allah